O trabalho do(a) assistente social em organizações da sociedade civil - Santos, Ana Carolina Vaz dos (2022)
This dissertation is about the work of social workers in Civil Society Organizations (CSOs). Its objective is to unveil how the work of social workers inserted in the work processes of these institutions conforms, in order to offer subsidies that contribute to the debate and improvement of professional skills from the perspective of meeting the demands in these socio-occupational spaces. Therefore, the research was methodologically developed based on a qualitative study, built under the framework of the dialectical and historical materialist method, with emphasis on the categories of totality, mediation, contradiction and historicity. Its data collection process used a combination of empirical sources, with online interviews with social workers working in CSOs linked to the National Social Assistance Policy; documentary, with an analysis of the work plans of the professionals who make up the study sample and bibliographical, based on a bibliographic review in dialogue with the mapping of the state of the art on the subject. Data were processed and analyzed based on content analysis. The main results denote the contradictions between the limits and possibilities of the work of social workers in the CSOs surveyed, which comes up against limitations such as the fragile mediation between theory, instruments and techniques by the professionals and the accentuated process of precarious conditions work at the institutional level. But it finds possibilities to contribute, from professional insertion, to the strengthening of the users through access to rights and mechanisms of popular participation, thus promoting processes of construction of a less unequal, more democratic and participatory society that is consistent with the ethical and political direction of the profession. The results obtained are important to build knowledge that contributes to the improvement of interventions in this socio-occupational space, considering the scarcity of theoretical productions in the area of Social Work on the subject and the progressive inclusion of professionals in these organizations. So, this study is relevant for providing opportunities for problematizations about the work of social workers in CSOs from the foundations of the profession to strengthen the professional ethos and critical intervention of the category.